Evaluation of the Heavy Metal Contents of Soil and Crops on a Field Treated with Ogun Rock Phosphate and Cowdung Fertilizers - Anwadike, Benjamin Chukwumah (2015)
Phosphate rock (PR) contains trace levels of Cadmium, Zinc, Arsenic and Lead, which could contaminate soil and plants following PR application alone and in combination with various levels of cowdung fertilizers. This study was designed with the aim to estimate the residual heavy metal contents of soil and crop following PR and cowdung fertilizer treatments. This was carried out with the view to determining the heavy metal contents of soil and plant samples in a field treated with PR fertilizer and to estimate the ideal PR and level of cowdung fertilizer combination with respect to Zn, Cu, Pb, Cb and As metal contamination of soil and crops.